Cross-cultural translation, validity, and reliability of the Turkish version of the Back Pain Attitudes Questionnaire - ÖZGÜL, BAHAR; SARI, ZÜBEYİR (ELSEVIER, 2022)
Background: As the Back Pain Attitudes Questionnaire (Back-PAQ), a validated instrument, could be performed to evaluate biopsychosocial dimensions of back pain, it has not been translated and adapted for Turkish population. Objectives: It was aimed to translate and cross-culturally adapt the Back-PAQ (versions of 34-item, 20-item, and 10-item) into Turkish language and analyse the validity and reliability of the Back-PAQ-Turkish version (Back-PAQ-Tr). Study design: Study of diagnostic accuracy/assessment scale. Methods: The translation and cross-cultural adaptation process were carried out in several steps according to international best-practice guidelines. 173 participants with back pain were recruited. Turkish version of the Tampa Scale of Kinesiophobia (TSK-Tr) and Fear Avoidance Beliefs Questionnaire (FABQ-Tr) were used to investigate the convergent validity. Results: Internal consistency of the Back-PAQ-Tr, Back-PAQ-Tr-20, and Back-PAQ-Tr-10 were 0.82, 0.78 and 0.68, respectively. Test-retest reliability was excellent for Back-PAQ-Tr (ICC = 0.95) and Back-PAQ-Tr-20 (ICC = 0.95), but weak for Back-PAQ-Tr-10 (ICC = 0.50). A weak correlation was found between all versions of Back-PAQ-Tr and TSK-Tr & FABQ-Tr, except for the moderate correlation between Back-PAQ-Tr-10 and TSK-Tr (r = -0.51) & the physical activity score of FABQ-Tr (r = -0.51). Back-PAQ-Tr, Back-PAQ-Tr-20, and Back-PAQ-Tr-10 accounted for 66.2%, 60.5%, and 78.2% of the variance in the data set, respectively. Conclusion: The versions of 34-item and 20-item Back-PAQ-Tr are reliable and valid questionnaire to assess Turkish populations' attitudes and beliefs regarding back pain. Since the reliability of the 10-item version was determined to be quite low, we particularly recommend the use of the versions of Back-PAQ-Tr and Back-PAQ-Tr-20.
Keywords: Back pain; Questionnaire; Attitudes; Cross-cultural adaptation; AVOIDANCE BELIEFS QUESTIONNAIRE; FEAR-AVOIDANCE; MUSCULOSKELETAL-PAIN; ADAPTATION; DISABILITY; RISK; METAANALYSIS; PREVALENCE; CRITERIA; SCALE